Great Policy Successes - 't Hart, Paul (Oxford University Press, 2019)
"With so much media and political criticism of their shortcomings and failures, it is easy to overlook the fact that many governments work pretty well much of the time. Great Policy Successes turns the spotlight on instances of public policy that are remarkably successful. It develops a framework for identifying and assessing policy successes, paying attention not just to their programmatic outcomes but also to the quality of the processes by which policies are designed and delivered, the level of support and legitimacy they attain, and the extent to which successful performance endures over time. The bulk of the book is then devoted to 15 detailed case studies of striking policy successes from around the world, including Singapore's public health system, Copenhagen and Melbourne's rise from stilted backwaters to the highly liveable and dynamic urban centres they are today, Brazil's Bolsa Familia poverty relief scheme, the US's GI Bill, and Germany's breakthrough labour market reforms of the 2000s. Each case is set in context, its main actors are introduced, key events and decisions are described, the assessment framework is applied to gauge the nature and level of its success, key contributing factors to success are identified, and potential lessons and future challenges are identified. Purposefully avoiding the kind of heavy theorizing that characterizes many accounts of public policy processes, each case is written in an accessible and narrative style ideally suited for classroom use in conjunction with mainstream textbooks on public policy design, implementation, and evaluation.